Depressive symptoms differ across Physical Activity Status based on comorbid anxiety and depression status among adolescents. (October 2020) - Forte, Chloe; McDowell, Cillian; MacDonncha, Ciaran; Herring, Matthew P.
Abstract: Statement of problem: Comorbid anxiety and depression is increasingly prevalent in adolescents, and comorbidity results in greater symptom severity and duration. Our previous reports support positive benefits of physical activity (PA) for depressive symptoms among adolescents (see Mcdowell, MacDonncha, & Herring, 2017). However, the impact of comorbid anxiety on PA, depressive symptoms, and their associations is unknown. It is plausible that comorbid anxiety may be an important consideration when examining associations between PA and depressive symptoms. Thus, we critically expand our previous report by investigating differences in depressive symptoms across PA status based on comorbid anxiety and depression status. Methods: Adolescents (N = 481; 200 female) aged 15.1 ± 1.7 y self-reported PA status; low, moderate, and high PA were classified based on ≥60 min s of PA 0–2, 3–4, and ≥5 d/wk, respectively. The Quick Inventory of Depressive Symptomatology assessed depressive symptoms (≥6 classified as depressed). The Trait subscale of the State-Trait Anxiety Inventory assessed anxiety symptoms (≥50 classified as anxious). Two-way ANCOVA was followed by Bonferroni-adjusted simple effects analyses. Results: The interaction between PA and comorbid status was statistically significant ( p < 0.001). Depressive symptoms were significantly higher for comorbid anxiety with low ( p ≤ 0.007) and high PA ( p ≤ 0.003) compared to moderate PA, significantly higher for comorbid anxiety compared to depression-only for low ( p < 0.001) and high PA ( p < 0.001), and non-significantly higher for moderate PA ( p > 0.30). Conclusion: Depressive symptoms differed across PA levels based on comorbid anxiety status. Highlights: Comorbid anxiety may influence association between physical activity and depression. 481 adolescents self-reported physical activity and anxiety and depressive symptoms. Depressive symptoms were highest among those with comorbid anxiety and depression. Depressive symptoms were highest among those with comorbid anxiety with low activity. Comorbid anxiety may influence PA benefits for depressive symptoms.